Nghiên cứu khả năng sinh tổng hợp IAA của chủng RH - Nguyễn, Thị Kim Quy (2017)
Hội nghị khoa học nữ lần thứ 4, Hà Nội, 1999 -- Lần thứ 5, Hà Nội, 2000 -- Lần thứ 6, Hà Nội, 2001 -- Lần thứ 7, Hà Nội, 2002 -- Lần thứ 8, Hà Nội, 2003 -- Lần thứ 9, Hà Nội, 2004 -- Lần thứ 10, Hà Nội, 2005.